2021
DOI: 10.1186/s12981-021-00396-2
|View full text |Cite
|
Sign up to set email alerts
|

A realist evaluation of the continuum of HIV services for men who have sex with men

Abstract: Background Men who have Sex with Men (MSM) represent the risk group that are disproportionately most affected by the human immunodeficiency virus (HIV) and continue to drop-off from the steps of the continuum of HIV services that have been adopted to overcome poor engagement and retention in care. This realist evaluation aimed at: (1) describing the evaluation carried out in Haiti aiming to ascertain why, how and under which circumstances MSM are linked and retained along the continuum, (2) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Quinn, Dickson-Gomez, et al, 2019; Sang et al, 2023; Sullivan & Eaton, 2021). These stigmas can also affect MSM living with HIV by dissuading men from accessing HIV care and treatment (Arnold et al, 2014; Dunbar et al, 2021; Haile et al, 2011). Sexuality-based anticipated health care stigma may also constrain HIV care engagement for MSM, as anticipated health care stigma related to attributes such as substance use and HIV status has been associated with decreased engagement in HIV care for this population (Batchelder et al, 2021; Camacho et al, 2020; Mitzel et al, 2015; K.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Quinn, Dickson-Gomez, et al, 2019; Sang et al, 2023; Sullivan & Eaton, 2021). These stigmas can also affect MSM living with HIV by dissuading men from accessing HIV care and treatment (Arnold et al, 2014; Dunbar et al, 2021; Haile et al, 2011). Sexuality-based anticipated health care stigma may also constrain HIV care engagement for MSM, as anticipated health care stigma related to attributes such as substance use and HIV status has been associated with decreased engagement in HIV care for this population (Batchelder et al, 2021; Camacho et al, 2020; Mitzel et al, 2015; K.…”
Section: The Present Studymentioning
confidence: 99%
“…Recent research has demonstrated how sexuality-based family stigma may act as a potential barrier to PrEP awareness and uptake among MSM (Dunbar et al, 2021;Farley et al, 2022), while studies examining sexuality-based social stigma have been mixed, with both negative and positive associations with PrEP engagement being reported (Dunbar et al, 2021;Farley et al, 2022;Matacotta et al, 2020;K. Quinn, Bowleg, et al, 2019;Sang et al, 2023;Sullivan & Eaton, 2021).…”
mentioning
confidence: 99%
“…For the past three decades, national HIV strategic responses have been instrumental in reducing Haiti’s HIV prevalence from 6.2% in 1993 to 1.9% in 2020 3 , 4 . As the country continues to make progress towards controlling the epidemic and expanding access to antiretroviral therapy (ART), Men who have Sex with Men and Women (MSMW), are largely left out of the discussion of key populations 5 7 . Yet according to a survey conducted and published by the United Nations, the HIV prevalence among MSMW was 18.2% in 2017, making them the most underserved population in terms of HIV prevention and care 4 .…”
Section: Introductionmentioning
confidence: 99%
“…As MSMW are highly stigmatized by both religious and social norms, homosexual practices are often driven underground. Perpetuated at the community level, violence toward MSMW is sometimes overlooked by the police force 7 . Moreover, access to HIV prevention and treatment services remain limited due to fear of non-voluntary disclosure and the fact that healthcare providers are perceived as judgmental and unable to respect confidentiality 5 , 12 .…”
Section: Introductionmentioning
confidence: 99%